2019
DOI: 10.1155/2019/2192093
|View full text |Cite
|
Sign up to set email alerts
|

Resistin in Human Seminal Plasma: Relationship with Lipid Peroxidation, CAT Activity, GSH/GSSG Ratio, and Semen Parameters

Abstract: Resistin is an adipokine involved in inflammation and able to induce the expression of other proinflammatory cytokines. It is known that, in human semen, resistin is correlated with inflammatory cytokines and sperm quality. The aim of this prospective study was to explore the potential relationship between resistin, lipid peroxidation (LPO), catalase (CAT) activity, and reduced and oxidized glutathione (GSH/GSSG) ratio in semen samples of infertile patients with leukocytospermia (no. 19), infertile patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The results of this research matched those reported in the literature concerning the negative relationship between semen cytokine concentrations and sperm parameters [ 5 , 6 , 34 ]. There is clear evidence that cytokines influence spermatozoa functions and can modulate pro-oxidant and antioxidant activities in the male genital tract [ 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…The results of this research matched those reported in the literature concerning the negative relationship between semen cytokine concentrations and sperm parameters [ 5 , 6 , 34 ]. There is clear evidence that cytokines influence spermatozoa functions and can modulate pro-oxidant and antioxidant activities in the male genital tract [ 35 ].…”
Section: Discussionsupporting
confidence: 88%
“…Oxidative stress, resulting from an imbalance between ROS production and antioxidant defenses, contributes to aging and the pathogenesis of numerous diseases including neurodegenerative diseases [30][31][32][33]. SOD, CAT and GSH-PX are antioxidant enzymes that contribute importantly to cells' capacity for surviving oxidative stress [34,35]. The severity of oxidative stress in cultured cells can be assessed by measuring intracellular ROS, LPO and MDA, as well as by measuring the release of LDH from cells to the medium.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong relationship between VCL and sperm dysfunctions [ 7 , 36 , 37 ]. By altering the normal testis physiology, VCL disrupts spermatogenesis that leads to low spermatozoa quantity and quality [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Reza et al [9] and Watcho et al [16] reported, respectively, that P. microphylla and D. arborea increased the testis and epididymis weights of VCL rats. ere is a strong relationship between VCL and sperm dysfunctions [7,36,37]. By altering the normal testis physiology, VCL disrupts spermatogenesis that leads to low spermatozoa quantity and quality [11].…”
Section: Discussionmentioning
confidence: 99%